Effects of Different Rotation Combinations of Cabbage, Kidney Bean and Maize on Soil Fungal Communities and Soil Nutrients - Tianle Wang; Xiaojuan Wang; Ling Xie (Agronomy, 2023)
The continuous cropping of cabbage or kidney bean results in a decrease in yield by influencing the soil environment. To decrease the damage caused by continuous cropping, ten treatments of cabbage–maize–cabbage (CMC), kidney bean–maize–cabbage (BMC), cabbage–cabbage–cabbage (CCC), cabbage–maize–kidney bean (CMB), kidney bean–maize–kidney bean (BMB), kidney bean–kidney bean–kidney bean (BBB), cabbage–cabbage–maize (CCM), cabbage–kidney bean–maize (CBM), kidney bean–kidney bean–maize (BBM) and kidney bean–cabbage–maize (BCM) rotation combinations were set up. The changes in soil nutrients, fungal community structure, composition and diversity in topsoil under the ten crop rotation combinations were analyzed using Illumina NovaSeq high-throughput sequencing technology and chemical technology. Fungal species were abundant in the ten treatments. The OTUs (operational taxonomic units) showed no significant differences. The richness index values of each treatment had significant differences. The diversity index value of the CCC treatment was significantly lower than those of the other treatments. The dominant soil fungal phylum was Ascomycota, and the subordinate soil fungal phylum was Basidiomycota. No significant differences were observed in Ascomycota between the treatments. Basidiomycota in the BBM treatment was significantly higher than that in the CCM treatment. Kickxellomycota was not found in the CCM and CCC treatments. The BBM treatment had no Entorrhizomycota. The dominant soil fungal class belonged to Ascomycota. The common distinction between continuous cropping and crop rotation was Diaporthales, which might be the main fungal order causing continuous cropping disorders. As the best choice, the BBM treatment could prevent soil-borne fungal diseases and provide the basis for the rational crop rotation of cabbage, kidney bean, and maize.